Oscuridad del ser by Casa Arte: producción de arte y vestuario inspirado en la obra Vampyr de Carolina Andújar - Rodríguez Gómez, Clara Elena (Universidad de San Buenaventura - Cali, 2018)
The present grade work takes as an intention to generate the base of an idea of business focused on the art, especially on the theatrical wardrobes and its adaptability to be used in other contexts. These pledges (suits of scene) generally lose its value once its intention is fulfilled in the stage, for this reason it is pertinent to generate a method that could prolong its use and contribute major value in these pledges. A project that there thinks about how to include the art in all its context, fuse the different artistic disciplines under the identity of Concept Store and reaffirm the importance of the designer like creative, artistic and generating producer of sustainable solutions in the design.